(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce (r, s)-δ-fuzzy closed sets in double fuzzy topological spaces and investigate some of their properties. Moreover, we introduce the concept of double fuzzy δ-continuous functions. Several interesting properties and characterizations are introduced and discussed. Furthermore, the relationships among the new concepts are introduced and established with some interesting counterexamples.